Building Resilient Campuses: A Blueprint in Proposing Safe Spaces to Address Sexual Grooming in Academia - Junry G. Tianzon; Zenaida Villacete; Leany Barasi; Janalyn Salvador; Hernando L. Bernal Jr. (RIRAI Publisher, 2024)
ABSTRACT The study delves into the intricate matter of sexual grooming in academic settings and proposes a comprehensive approach to intervention and prevention. Using qualitative approaches, this study assesses the prevalence of grooming incidents, identifies recurrent themes, and investigates the repercussions on victims and educational communities. Along with providing research-based recommendations for curriculum developers, school administrators, and other interested parties, the study also critically evaluates present methods. This study aims to provide useful guidance for establishing a secure and supportive learning environment for all involved. The results of this study indicate that the respondents were not very aware of the risks associated with sexual grooming. This can lead to negative outcomes such as manipulating, exploiting, and abusing children and young people when someone establishes a relationship and gain their trust. Due to the fact that many students especially women prefer older guys, sexual grooming is becoming increasingly common in academic settings. First of all, they consider them to be more relationship-savvy, especially those who are employed or have enough money, they feel as though they are protected and can somehow care for their needs—funds taken from their stipends. Younger partners believe that because the elder partner is more experienced, s/he can mentor and teach them in a variety of areas. From the perspective of the more senior person in the relationship, they prefer dating a younger partner since they perceive themselves as the dominant party. Additionally, they think that making the